Resistance Studies, in vitro Model, of Myeloid Leukemia Cell Lines HL-60 Against Thymoquinone and Doxorubicin in the Presence of Type I Collagena - Ghali, Rabeb; Mahjoub, Sana; Bahia, Wael; Chaieb, Vera; Achour, Bechir; Janhani, Faouzi; Mahjoub, Touhami (Journal of Hematology Research, 2017)
Purpose: The prognostic of Acute leukemia is cell drug resistance dependent, which is principal cause of death. The bone marrow microenvironment is directly implicated as source of chemio resistance. Several researchers have studied in vivo and vitro the effect of the bioactive molecules such as the Thymoquinone (TQ) on cancers chemo resistant. The aim of this study is to compare the activities of Thymoquinone to Doxorubicin on presence and on absence of collagen type I, which is the major component of cell extra matrix (CEM). Methods: Cell line HL60 resistance against Doxorubicin and Thymoquinone was tested on presence and on absence Type I collagen at concentration 25, 50 and 100 µg /cm2 TQ and Dox cytototoxicities was evaluated with counting using KOVA Glasstic Slide and phase contrast microscopy. HL-60 cells were seeded at 10 cells/well for 24h in the presence or not of collagen and treated or not with 200nM of Dox or 10 µM of TQ. After incubation, apoptosis was determined using Annex V and Dead Cell Assay kit (Millipore) and Caspase 3/7 Assay kit (Millipore). Results: cell line HL60 proliferation is more resistance against Doxorubicin in presence Type I collagen than Thymoquinone. Conclusion: Collagen induce cell HL60 resistance against Doxorubicin, But not against Thymoquinone. Combination Thymoquinone, bioactive molecule, to Doxorubicin can decrease the drug resistance and improve leukemia prognostic.